2006
DOI: 10.1111/j.1745-7254.2006.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium ferulate on amyloid-beta-induced MKK3/MKK6-p38 MAPK-Hsp27 signal pathway and apoptosis in rat hippocampus

Abstract: Aim: To observe the effects of sodium ferulate (SF) on amyloid beta (Aβ) 1-40 -induced p38 mitogen-activated protein kinase (MAPK) signal transduction pathway and the neuroprotective effects of SF. Methods: Rats were injected intracerebroventricularly with Aβ 1-40 . Six hours after injection, Western blotting was used to determine the expressions of phosphorylated mitogen-activated protein kinase kinase (MKK) 3/MKK6, phospho-p38 MAPK, interleukin (IL)-1β, phospho-MAPK activating protein kinase 2 (MAPKAPK-2), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…In addition, ferulic acid attenuates iron-induced oxidative damage and apoptosis in cultured neurons [14] and reduces the expression of inducible NOS and cyclooxygenase activity following exposure to lipopolysaccharides [15] . Our previous study showed that SF had protective effects from Aβ-induced neurotoxicity through the suppression of p38 mitogen-activated protein kinase and the upregulation of extracellular signal-regulated kinase (ERK) and Akt [16,17] . In the present study, we investigated the roles of the ERK pathway and phosphatidylinositol 3-kinase (PI3K) pathway in the neuroprotection by SF from glutamate toxicity.…”
Section: +mentioning
confidence: 99%
“…In addition, ferulic acid attenuates iron-induced oxidative damage and apoptosis in cultured neurons [14] and reduces the expression of inducible NOS and cyclooxygenase activity following exposure to lipopolysaccharides [15] . Our previous study showed that SF had protective effects from Aβ-induced neurotoxicity through the suppression of p38 mitogen-activated protein kinase and the upregulation of extracellular signal-regulated kinase (ERK) and Akt [16,17] . In the present study, we investigated the roles of the ERK pathway and phosphatidylinositol 3-kinase (PI3K) pathway in the neuroprotection by SF from glutamate toxicity.…”
Section: +mentioning
confidence: 99%
“…Also, sodium ferulate inhibited a b-amyloid-(1-40)-induced increase in phosphorylated-p38 mitogen-activated protein kinase (MKK3/MKK6), partly prevented a decrease in phosphorylated MAPKAPK2 and Hsp27 expression, and inhibited the activation of caspase cascades (caspase-3, caspase-7 and caspase-3 activities) (67). Sodium ferulate restored the arrangement and the number of hippocampal CA1 pyramidal neurons in the hippocampus of young adult rats subjected to b-amyloid-(1-40) (67) as well as the arrangement of hippocampal CA1 pyramidal neurons in the hippocampus of aged rats (68).…”
Section: Phenolic Acids As Efficient Ache and Bche Inhibitorsmentioning
confidence: 99%
“…Sodium ferulate is shown to prevent amyloid beta-induced mitogen-activated protein kinase kinase (MKK) 3/MKK6-p38 MAPK activity in rat hippocampus (Jin et al 2006), showing the suppression of the age-related Jun N-terminal kinase (JNK) pathway and upregulation of mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK)1/2 pathway in aged rat hippocampus (Jin et al 2008). In human umbilical vein endothelial cells (HUVECs), ferulate blocked the JNK pathway, but did not change the ERK (Ma et al 2010a).…”
Section: Introductionmentioning
confidence: 99%